Petrous Apex Cholesterol Granuloma: Importance of Pedicled Nasoseptal Flap in Addition to Silicone T-tube for Prevention of Occlusion of Drainage Route in Transsphenoidal Approach—A Technical Note - SHIBAO, Shunsuke (Neurol Med Chir (Tokyo), 2015)
Recently, petrous apex cholesterol granulomas (CGs) have been treated via the endoscopic endonasal transsphenoidal approach (EEA) using a silicone tube, to prevent drainage route occlusion. Occlusion of the drainage route has led to problems with recurrence. The aim of this report is to describe the use of a surgical technique to prevent drainage route occlusion. In surgical technique, the posterolateral wall of the sphenoid sinus was opened by EEA. After cyst debridement, a vascularized nasoseptal flap with a width of approximately 4 cm was inserted into the lumen with a silicone T-tube with a diameter of 7 mm. This technique was used in two patients: the first patient during the second operation after recurrence following occlusion of the drainage route, and the second patient during the first operation. Opening of the cyst wall was confirmed endoscopically in both patients 12–24 months after surgery, even after removal of the T-tube. In conclusion, the use of a pedicled nasoseptal flap with a silicone tube is useful to prevent CG recurrence, by paranasal cavitization of the cystic cavity.